Needs Assessment for Ergonomic Patient Repositioning Device Among Bedridden Patients: A Literature Review - Irma Darmawati; Agni Laili Perdani; Ridha Wahdini; Nadia Sintia Wardany (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Pressure ulcers remain a prevalent and preventable complication among bedridden patients, with manual repositioning every two hours established as the clinical standard of prevention. This practice places substantial physical demands on nurses and informal caregivers, contributing to high rates of work-related musculoskeletal disorders, including low back pain, among those performing repetitive turning tasks. Despite the availability of various assistive devices, most have been developed without systematic assessment of the combined needs of both patients and caregivers as dual users. Objective: This review aimed to identify clinical, ergonomic, and functional needs for a patient repositioning device among bedridden patients and their caregivers through synthesis of existing literature. Methods: A literature review was conducted using Scopus, PubMed, and EBSCO, covering publications from 2016 to 2024. Articles published in English addressing repositioning practices, assistive device design or evaluation, caregiver ergonomics, or pressure injury prevention in immobile patients were included. Studies unrelated to repositioning function or device ergonomics were excluded. Eight articles met the inclusion criteria and were included in the final synthesis. Results: Three primary need domains were consistently identified across the reviewed literature. First, bedridden patients require effective pressure redistribution to prevent tissue injury during prolonged immobility. Second, caregivers need a reduction in biomechanical workload during repositioning, particularly in lumbar and shoulder loading. Third, the device must offer usability features that enable safe, consistent positioning without requiring multiple personnel or specialized training. Current assistive devices inadequately address all three domains simultaneously, with most designs optimizing for one dimension at the expense of others. Conclusion: Bedridden patients and their caregivers present distinct yet interdependent needs that must be jointly addressed in ergonomic repositioning device development. A dual-user design framework integrating pressure redistribution, biomechanical efficiency, and practical usability represents a critical direction for future nursing research and device innovation.